Efektifitas Kulit Buah Kakao (Theobroma Cacao L) Sebagai Biosorben Terhadap Logam Pb dan Cd dan Anti Bakteri Terhadap Staphylococcus Aureus - Prasetyo, Dicky; Ifa, La; Yani, Setyawati (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of the concentration of cocoa peel biosorbent (Theobroma Cacao L) on the decrease of Pb & Cd Metals in AAS wastewater and to determine the effect of cocoa peel extract concentration in inhibiting the growth of Staphylococcus Aureus (S.Aureus) bacteria. Cocoa peel biosorbents were activated with HNO3 0.6 N. Biosorbents with masses of 5 grams, 10 grams and 15 grams were able to absorb Pb and Cd metals in the waste, which absorbed 1.7703 mg/L, 2.1428 mg/L and 2.4868 mg/L respectively from the initial concentration of waste which was 3.0069 mg/L. So that the absorption effectiveness was obtained at 58.87%, respectively. 71.26% and 82.70% where the largest absorption was with the addition of 15 grams of biosorbent and metal Cd in the waste, which were absorbed by 2.0100 mg/L, 2.3538 mg/L and 2.6499 mg/L respectively from the initial concentration of waste, which was 3.0024 mg/L. So that the absorption effectiveness was obtained which was 66.94%, 78.35% and 88.25%, respectively, where the largest absorption was with the addition of biosorbents of 15 grams.